Surveillance of antibiotic resistance in Neisseria gonorrhoeae in the WHO Western Pacific Region, 2006 - WHO Western Pacific Gonococcal AMR Surveillance Programme; Tapsall, John (Communicable Diseases Intelligence, 2008)
The World Health Organization Western Pacific Region Gonococcal Antimicrobial Surveillance Programme (WHO WPR GASP) examined approximately 8,400 isolates of Neisseria gonorrhoeae from 16 countries for resistance to relevant antibiotics in 2006. Antimicrobial resistance was at record levels in the region and poses major problems for the management of this important disease. High rates of resistance to penicillins and quinolones persisted. Gonococci ‘non-susceptible’ to third generation cephalosporins were found in several centres. There were infrequent instances of spectinomycin resistance. Commun Dis Intell 2008;32:48–51.